Length-dependent changes in contractile dynamics are blunted due to cardiac myosin binding protein-C ablation - Mamidi, Ranganath; Gresham, Kenneth S.; Stelzer, Julian E. (Frontiers in Physiology, 2014)
Enhanced cardiac contractile function with increased sarcomere length (SL) is, in part, mediated by a decrease in the radial distance between myosin heads and actin. The radial disposition of myosin heads relative to actin is modulated by cardiac myosin binding protein-C (cMyBP-C), suggesting that cMyBP-C contributes to the length-dependent activation (LDA) in the myocardium. However, the precise roles of cMyBP-C in modulating cardiac LDA are unclear. To determine the impact of cMyBP-C on LDA, we measured isometric force, myofilament Ca2+-sensitivity (pCa50) and length-dependent changes in kinetic parameters of cross-bridge (XB) relaxation (krel), and recruitment (kdf) due to rapid stretch, as well as the rate of force redevelopment (ktr) in response to a large slack-restretch maneuver in skinned ventricular multicellular preparations isolated from the hearts of wild-type (WT) and cMyBP-C knockout (KO) mice, at SL’s 1.9µm or 2.1µm. Our results show that maximal force was not significantly different between KO and WT preparations but length-dependent increase in pCa50 was attenuated in the KO preparations. pCa50 was not significantly different between WT and KO preparations at long SL (5.82±0.02 in WT vs. 5.87±0.02 in KO), whereas pCa50 was significantly different between WT and KO preparations at short SL (5.71±0.02 in WT vs. 5.80±0.01 in KO; p<0.05). The ktr, measured at half-maximal Ca2+-activation, was significantly accelerated at short SL in WT preparations (8.74±0.56s-1at 1.9µm vs. 5.71±0.40s-1at 2.1µm, p<0.05). Furthermore, krel and kdf were accelerated by 32% and 50%, respectively at short SL in WT preparations. In contrast, ktr was not altered by changes in SL in KO preparations (8.03±0.54s-1at 1.9µm vs. 8.90±0.37s-1at 2.1µm). Similarly, KO preparations did not exhibit length-dependent changes in krel and kdf. Collectively, our data implicate cMyBP-C is an important regulator of LDA via its impact on dynamic XB behavior due to changes in SL.